Coping Humor of Entrepreneurs: Interaction Between Social Culture and Entrepreneurial Experience - Lin, Song; Li, Jing; Han, Rui (Frontiers in Psychology, 2018)
It is feasible to deal with high pressure in entrepreneurship with humor. This paper studies the effect of interaction between entrepreneurs’ perception of social culture and entrepreneurial experience (including experience with entrepreneurial failure and current company performance) on coping humor of entrepreneurs with the sample of 171 entrepreneurs from Bohai Rim in China. Regression analysis revealed that entrepreneurs prefer coping with pressure with humor if they sense the favorable condition brought by social culture to entrepreneurship and their business is currently performing well or if they perceive a friendly culture to entrepreneurship and had once experienced entrepreneurial failure. This study contributes to the literature of the theory of humor, the culture of entrepreneurship, and entrepreneurial failure.